ANALYSIS OF MSME SALES STRATEGY IN THE DIGITAL ERA - Pandu Adi Cakranegara; La Ode Marihi; Dicky Jhon Anderson Butarbutar; Poetri AL-Viany Maqfirah; Irham Pakawaru (SEAN Institute, 2022)
Business competition in the digital era is one of the references for MSMEs to modify their sales strategies. Since technology applications, particularly in the field of transactions, have become an integral part of the ease of the transaction process, MSMEs cannot compete in terms of sales if their sales strategies do not keep up with digital era developments. In actuality, there are still several challenges for MSMEs, including inadequate capital, continued reliance on direct transactions, and an inability to use technology and the internet for optimizing market segmentation and growing new customers. This is also attributable to the varying e-commerce application skills of human resources. To address the challenges faced by MSMEs, the objective of this research is to provide alternative strategic recommendations for supporting sales success, such as optimizing the internet as a promotional medium and also optimizing the use of e-commerce for sales and transaction processes, implementing digital marketing to reach target markets, transformation mechanisms for online payments, enhancing product and service quality, and boosting customer loyalty through the use of loyalty programs.